Minimally invasive excision of aortic valve fibroelastoma - B.М. Тоdurov; M.D. Glagola; G.I. Darvish; O.G. Bitsadze; А.V. Ivanyuk; N.V. Shatelen; O.S. Bolgova; S.I. Dorofeeva (Кардіохірургія та інтервенційна кардіологія)
Papillary fibroelastoma is a rare primary tumor of cardiac origin accounting for approximately 7.9–10.0 % of all primary cardiac neoplasms. Due to high risk of fragmentation and thromboembolic complications emergency surgical excision is a standard of treatment in these patients even for asymptomatic cases. We describe the case of a 57 years-old lady using minimally invasive sternotomy. In this case we demonstrate that minimally invasive approach can provide acceptable safety and advantages compared to the conventional median sternotomy.